ORDEM E DESORDEM NA POLIARQUIA PÓS-ESTATAL: O PAPEL DA RESPONSABILIDADE SOCIOAMBIENTAL DAS EMPRESAS - Sampaio, José Adércio Leite; Pinto, João Batista Moreira Pinto; Fabel, Luciana Machado Teixeira (Veredas do Direito, 2021)
Globalization has revealed a new normative and decision-making dynamic, made up of various orders, systems and subsystems with claims of validity or mere effectiveness. Decision-making and political power is now shared among States, international organizations, public and parastatal entities, and transnational corporations. The challenge is to reconcile issues that overlap the borders of States, providing dialogue and the construction of plural spaces that favor the common good, respect for human and environmental rights. It is proposed that the state of anomie or relative ineffectiveness of the normativity of promoting these rights gives way to a cooperative public-private action regime and effective accountability of those who violate them. Corporate social responsibility, understood in the domain of the horizontality of human rights, can be an important step, associated with the recognition of plural and, at times, competing forums for imposing sanctions. In the end, the disorder of a delegitimized polyarchy of irresponsibility can be succeeded by the decentralized coordination of subsystems of dialogic normativity guided by a governance committed to human rights and environmental justice.